Yahoo Web Search

  1. Sort by

  1. Decomposing 1/[k(k+1)(k+2)], you have: A/k + B/(k+1) + C/(k+2) = 1/[k(k+1.... Therefore: A(k+1)(k+2) + B(k)(k+2) + C(k)(k+1) = 1 which must hold true for all valid values of k. To determine...

    2 Answers · Science & Mathematics · 08/09/2007

  2. y = x/(1 + kx) y(1 + kx) = x y + kxy = x kxy = x - y k = (x - y)/(xy) I could have sworn I already answered this one!

    4 Answers · Science & Mathematics · 08/02/2010

  3. Note that Σ(k = 5 to ∞) C(k-1, k-5) k^3/2^k...to ∞) (k-1)(k-2)(k-3)(k-4) * k^3 x^k {at x = 1/2} = (1/24) x^5 * Σ(k...%29+C%28k-1%2C+k-5%29+k^3%2F2^k I hope...

    1 Answers · Science & Mathematics · 29/07/2014

  4. 0=< k =<4 points of intersection are (-1,1) and (-3,1...solve it with 2 quadratic equations, one for each point. You will get k. For (-1,1), k is between (0,2) For (-3,1), k is...

    2 Answers · Science & Mathematics · 02/09/2008

  5. 2kx² - 12x + (k+7) = 0 Solve for k b² - 4ac = 0 (b = -12, a = 2k and c = k...8 ..........-k² - 7k + 18 = 0 .......... k² + 7k - 18 = 0 ........ (k - 2) (k + 9) = 0 ......k - 2 = 0.......................... k + 9 = 0 k - 2 + 2 = 0 + 2...

    4 Answers · Science & Mathematics · 12/09/2010

  6. If k is even, k = 2j for some j ≥ 1, then Γ(k/2) = Γ(j) = (j - 1)! If k is odd, k = 2j + 1 for some j ≥ 1, then by repeated application of the...

    2 Answers · Science & Mathematics · 29/12/2012

  7. Hello, x³ – (k + 1)x + 2k = 0 = = = = = = = = = = = = = = = = = = = = = = Obviously, if k=0, we obtain... prime and k≠0: Then 2k has four divisors: 1, 2, k and 2k. Rational root theorem induce that if a rational root exists...

    2 Answers · Science & Mathematics · 10/12/2012

  8. Goal: To get "k" isolated by itself. a.) 0 = 14 + k In order to isolate... so that the 3.3 on the variable side will turn into 0 and will not count. -0.8 = k + 3.3 -0.8 - 3.3 = k + 3.3 - 3.3 -4.1 = k + 0 Since the zero does...

    3 Answers · Science & Mathematics · 16/06/2011

  9. a(n) = Σ(k = 0 to ∞) 10^(-k^2) is irrational (choice C, assuming you mean...bit more, showing that it is transcendental. Let p(n) = Σ(k = 0 to n) 10^(n - k^2) and q(n) = 10^n. Then, |Σ(k = 0 to ∞) 10...

    2 Answers · Science & Mathematics · 13/04/2013

  1. Ad
    related to K
  1. Try asking your question on Yahoo Answers